(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This paper explores and demonstrates why the different systems and models of justice which the Organisation of African Unity (OAU) and the African Union (AU) respectively established are unstable. The OAU Charter did not create a court of justice, but a Mediation, Conciliation and Arbitration Commission to arbitrate disputes. Similarly, the African Charter on Human and Peoples’ Rights did not establish a court of law, but the African Commission on Human and Peoples’ Rights, whose recommendations are not binding. To address issues arising from the nonbinding nature of the Commission recommendations, the OAU adopted the Protocol Establishing the African Court on Human and Peoples’ Rights in Ouagadougou in 1998, whose decisions are binding. However, in the meantime, the OAU was replaced by the AU before the Court effective establishment. For its part, the Constitutive Act of the African Union (AU), which replaced the OAU Charter in 2000, provided for its own Court of Justice, which was established three years later by a protocol adopted in Maputo in 2003. Thus, two separate and specialised courts were to exist in parallel at the continental level. For reasons of rationalisation, the two protocols establishing these two courts were merged and replaced by the 2008 Sharm El-Sheikh Protocol, which created the African Court of Justice and Human Rights. The internal structure and competences of this future and unique Court were finally revised and amended by the Protocol adopted in Malabo in 2014: a criminal section, competent for 14 categories of crimes, was inserted within the projected Court. The AU’s judicial system is, to date, unstable and uncertain, especially as the 2008 and less realistic 2014 reforms raise more questions than they resolve. The doctrinal, analytical, and historical methods of legal research have shown that the latter two reforming Protocols – that of 2008 and 2014 respectively – may not enter into force because of the normative and procedural implications and consequences for both the status, competences and composition of the original Court and the judicial protection of human rights across the African continent.